Arah Dan Politik Hukum Bisnis Islam Di Indonesia - Siregar, Bonanda Japatani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Islamic Business Law is a legal dimension in business activities that is based on Islamic law. Law is understood as a set of rules that have sanctions and are made by the authorities in order to create peace in society. Islamic law as a legal system that comes from Allah Ta'ala has the same function, namely to provide benefit to society. Islamic law has a distinctive characteristic that is not only limited to benefit in this world but also safety in the hereafter. By explaining the development of business law, as well as involving it in legal policy and practice in Indonesia, it becomes more open to the possibility of a paradigm shift and more alternative ideas that can be contributed to the study of law in Indonesia, both at the level of establishing, implementing or enforcing law and analyzing doctrine and test the legitimacy of a social system and certain policies. Based on the background above, there is identification of the problem, namely First, how is the development of Islamic business law in the Indonesian political system, second, how is the influence of Islamic business law in Indonesia. The research used is a normative juridical research method, namely studying legal principles and analyzing problems, studying and analyzing through an approach to legal principles and statutory regulations with reference to the 1945 Constitution and Law No. 21 of 2008 concerning Sharia Banking and Law Number 33 of 2014 concerning Guarantees for Halal Products. Political legal factors in the causal relationship between law and legal politics are determinant in the sense that political activities are regulated by and must be subject to legal rules. Legal development contains the characteristics of a very dominant role of state institutions in determining the direction of legal development in a society. Legal products always develop in tune with the development of political configurations for the benefit of the economic growth of a city and a country.